2007
DOI: 10.1037/0735-7044.121.1.120
|View full text |Cite
|
Sign up to set email alerts
|

Choline supplementation following third-trimester-equivalent alcohol exposure attenuates behavioral alterations in rats.

Abstract: Despite the known adverse consequences of prenatal alcohol exposure, some pregnant women continue to drink alcohol, making it imperative to identify treatments for children with fetal alcohol spectrum disorders. The authors recently reported that perinatal choline supplementation can reduce some fetal alcohol effects (J. D. Thomas, M. Garrison, & T. M. O'Neill, 2004), and the present study examined whether choline supplementation is effective when administered after third-trimester-equivalent ethanol treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
160
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(185 citation statements)
references
References 93 publications
24
160
1
Order By: Relevance
“…An examination of the groups separately revealed that small effect sizes and sample sizes would have to have been inordinately large to confidently draw conclusions from the results; in addition, the possibility of a type II error could not be ruled out (achieved power ranged from 0.13 to 0.84). The null findings of this clinical trial were unanticipated because of the strong evidence that has suggested beneficial effects of choline supplementation in animal models of both typical development (39) and prenatal alcohol exposure (3)(4)(5)(6)(7)(8)10). However, this investigation was only one of a few trials to translate the aforementioned animal research to a human clinical trial of choline supplementation in FASDs, and previous studies, at earlier ages, have suggested some positive beneficial effects (13,14).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…An examination of the groups separately revealed that small effect sizes and sample sizes would have to have been inordinately large to confidently draw conclusions from the results; in addition, the possibility of a type II error could not be ruled out (achieved power ranged from 0.13 to 0.84). The null findings of this clinical trial were unanticipated because of the strong evidence that has suggested beneficial effects of choline supplementation in animal models of both typical development (39) and prenatal alcohol exposure (3)(4)(5)(6)(7)(8)10). However, this investigation was only one of a few trials to translate the aforementioned animal research to a human clinical trial of choline supplementation in FASDs, and previous studies, at earlier ages, have suggested some positive beneficial effects (13,14).…”
Section: Discussionmentioning
confidence: 83%
“…Notably, our group was the first, to our knowledge, to examine the effects of a nutritional intervention of choline with the use of a rodent model of FASDs (3). Through a series of studies, we showed that choline reduces the severity of alcohol's adverse effects on behavioral development whether administered perinatally (4,5) or postnatally after alcohol exposure has occurred (3,6,7). Choline mitigates behavioral deficits on tasks that depend on the functional integrity of the hippocampus and prefrontal cortex including spatial learning and memory (8), hyperactivity (8), trace classical conditioning (9,10), and working memory (3).…”
Section: Introductionmentioning
confidence: 99%
“…While this study examined only the neuroprotective effects of prenatal choline supplementation, some reported neuroprotective actions of choline appear to be postnatal (Thomas et al, 2007); thus, infants at risk for seizures might benefit from added choline to formula or choline supplementation to mother's diet. These data also suggest that prenatal choline deficiency may make offspring more vulnerable to the deleterious consequences of seizures, though this remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal and early postnatal choline supplementation has also been shown to protect against impairments in performance on hippocampal-dependent tasks caused by aging (Meck et al, 1988(Meck et al, , 1989Meck & Williams, 2003;McCann et al, 2006) or neonatal alcohol exposure (Thomas et al, 2004(Thomas et al, , 2007Wagner & Hunt, 2006). While the mechanism by which prenatal choline supplementation confers neuroprotection is not fully understood, choline is a vital nutrient important for several biological functions: acetylcholine synthesis, building biological membranes, cell signaling, and methyl donation (Blusztajn, 1998;Zeisel, 2004Zeisel, , 2006.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…In terms of neuroplasticity, adult hippocampal slices from prenatally choline supplemented rats exhibit a lower threshold for the induction of long-term potentiation compared with slices from control rats (Jones et al, 1999;Pyapali et al, 1998). Furthermore, perinatal choline supplementation can alter behavior and neurochemistry following a variety of developmental disorders, including the alleviation of behavioral abnormalities associated with fetal alcohol syndrome in Sprague-Dawley rats (Thomas et al, 2000(Thomas et al, , 2004(Thomas et al, , 2007Wagner and Hunt, 2006), attenuation of some of the motor deficits observed in a Mecp21 lox mouse model of Rett syndrome (Nag and Berger-Sweeney, 2007), and the improvement of sensory gating in a DBA/2 mouse model of schizophrenia that exhibits reduced numbers of hippocampal α7 nicotinic receptors (Stevens et al, 2007). Consequently, it was of interest in the present study to investigate the effects of prenatal choline supplementation on the implementation of S1 and S2 response thresholds involved in duration discrimination tasks such as the PI procedure due to the potential sensorimotor enhancing actions of α7 nicotinic receptor agonists during early development (Meyer et al, 1998).…”
Section: Introductionmentioning
confidence: 99%